Le lussazioni dell’arto superiore in età evolutiva - Toniolo, R.M.; Giordano, M.; Aulisa, A.G. (Lo Scalpello - Journal, 2018)
UPPER LIMB DISLOCATIONS IN THE DEVELOPING SKELETONChildren have a high propensity to injure their upper limbs. Younger children use their hands to discover and get toknow the world around them, while older ones and the teenagers are increasingly dealing with recreational physicalactivities and agonistic sports events. Upper extremity lesions may occur from the shoulder to the fingers. As regardsthe biomechanical features in the developing skeleton, bones and physes are usually involved while, on the other hand,dislocations and subluxations of the upper extremities are uncommon in children, because of the relative weakness ofthe epiphyseal plates. Correct diagnostic procedures and consequent therapeutic treatments are fundamental toachieve the best possible outcome.